Breakdown-limited endurance in HZO FeFETs: Mechanism and improvement under bipolar stress - Toprasertpong, Kasidit; Takenaka, Mitsuru; Takagi, Shinichi (Frontiers in Electronics, 2022)
Breakdown is one of main failure mechanisms that limit write endurance of ferroelectric devices using hafnium oxide-based ferroelectric materials. In this study, we investigate the gate current and breakdown characteristics of Hf0.5Zr0.5O2/Si ferroelectric field-effect transistors (FeFETs) by using carrier separation measurements to analyze electron and hole leakage currents during time-dependent dielectric breakdown (TDDB) tests. Rapidly increasing substrate hole currents and stress-induced leakage current (SILC)-like electron currents can be observed before the breakdown of the ferroelectric gate insulator of FeFETs. This apparent degradation under voltage stress is recovered and the time-to-breakdown is significantly improved by interrupting the TDDB test with gate voltage pulses with the opposite polarity, suggesting that defect redistribution, rather than defect generation, is responsible for the trigger of hard breakdown.